A tool to analyze delusions in a nonclinical population: Peter’s delusionalInventory (PDI-21) - ERYİĞİT, DERYA; CANEL, AZİZE NİLGÜN (My University, 2023)
The purpose of this study is to culturally adapt the Peter’s Delusional Inventory (PDI-21), originally developed by Peters, Joseph, and Garety (1999), for use in the Turkish context. A total of 674 participants participated in the data collection process. To provide a more culturally informed framework for the scale, an exploratory factor analysis (EFA) was conducted, resulting in the identification of 21 subscales. This scale structure underwent confirmatory factor analysis (CFA) to examine its six-component structure in a sample of university students. The results indicated that the 21- factor model demonstrated a satisfactory level of fit. To establish the criterion validity of Peter's Delusion Inventory, the EPQR-A scale, which is believed to assess similar constructs, was employed. The findings of the Pearson correlation analysis revealed a statistically significant positive association between the two measures (r=.35; p<.001). The study yielded a Cronbach's alpha coefficient of.81, indicating a high level of internal consistency. The ratio of Chi-square to degrees of freedom (χ 2 /df = 2.08), which was employed to assess the overall adequacy of the model, fell within the acceptable range. The root mean square error of approximation (RMSA) value for the model was determined to be 0.057. In this particular context, it was observed that the model exhibited a satisfactory level of conformity to the covariance matrix. Upon examination of the SRMR value, it was observed that it equaled 0.03, indicating a highly satisfactory fit. The NFI value of 0.92, which was higher than the threshold of 0.90, indicated that the model had a strong fit. The CFI score of 0.96 indicated that the model had a high level of fit. Based on these scores, it can be said that the Turkish form of PDI-21 is a valid and reliable tool.
Keywords: Delusional beliefs; validity; reliability; scale adaptation